Pengaruh Model Pembelajaran Kooperatif TGT (Teams Games Tournament) terhadap Keterampilan Menulis Ringkasan pada Siswa Kelas VI UPT SD 242 Gresik - Fauziatur Rohmah; Afakhrul Masub Bakhtiar; Ismail Marzuki (STIKes Ibnu Sina Ajibarang, 2025)
This research aims to determine the effect of the TGT (Teams Games Tournament) cooperative learning model on summary writing skills in class VI students at UPT SD 242 Gresik for the 2024/2025 academic year. The method used in this research is a pure experimental method (TrueExperiment). The research subjects were class VI students at UPT SD 242 Gresik consisting of two groups, namely the experimental group was given treatment using the TGT cooperative learning model and the control group was not given treatment. The instrument used in this research is a test summarizing explanatory text which has been tested for validity and reliability. The data obtained was analyzed using statistical tests. Based on the results of the analysis that has been carried out, there is a significant difference between the experimental group and the control group. This can beproven from theresultsofhypothesis testing intheresearch which showsa sig value of 0.000 < 0.05 so that H_0 is rejected and H_α is accepted. It can be concluded that there is an influence of the application of the TGT (Teams Games Tournament) cooperative learning model on summary writing skills in class VI students at UPT SD 242 Gresik.